PENGETAHUAN AKUNTANSI SEBAGAI PEMEDIASI HUBUNGAN ANTARA PENGALAMAN USAHA TERHADAP PENGGUNAAN LAPORAN INFORMASI AKUNTANSI - Yuli Prastyatini, Sri Lestari; Gabriella, Agatha Mutiara (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study examines the effect of business experience on accounting knowledge, the effect of accounting knowledge on the use of accounting information reports, the effect of business experience on the use of accounting information reports through accounting knowledge, the effect of business experience on the use of accounting information reports. The population in this study included Micro, Small and Medium Enterprises (MSMEs) in Bakpia Pathok Yogyakarta with a sample of 92 people. Data analysis using multiple linear regression analysis. The results of hypothesis testing show that business experience has a significant effect on accounting knowledge, accounting knowledge has a significant positive effect on the use of accounting information reports, business experience has a positive effect on the use of accounting information reports through accounting knowledge, business experience has a significant effect on accounting knowledge.